Behind the aid brand: Distinguishing between development finance and assistance - James Copestake (University of Bath, Centre for Development Studies (CDS), 2013)
International aid is often analysed as if it was a homogeneous product exclusively distributed between a relatively small numbers of public agencies. In contrast, this paper contributes to thinking about aid as a quasi-market with many different suppliers, users, channels, products and brands. More specifically, it suggests drawing a stronger distinction between development finance and development assistance. A simple graph shows how this entails distinguishing between social impact and financial sustainability. Given that these characteristics are often far from transparent, the paper also illustrates the limitations of a rational choice approach to analysing aid. The difficulties entailed in assessing aid impact and sustainability help to explain why brand reputations matter. The argument is illustrated with references to UK aid, aid to Ethiopia, and NGO promotion of smallholder linkages into agricultural value chains in Africa.
Keywords: 330; International aid; Brands; Development finance; Development assistance; Social impact; Financial sustainability; Smallholder agriculture; NGOs; Ethiopia